2014
DOI: 10.1371/journal.pone.0106452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Biotope on the Tick Infestation of Cattle and on the Tick-Borne Pathogen Repertoire of Cattle Ticks in Ethiopia

Abstract: BackgroundThe majority of vector-borne infections occur in the tropics, including Africa, but molecular eco-epidemiological studies are seldom reported from these regions. In particular, most previously published data on ticks in Ethiopia focus on species distribution, and only a few molecular studies on the occurrence of tick-borne pathogens or on ecological factors influencing these. The present study was undertaken to evaluate, if ticks collected from cattle in different Ethiopian biotopes harbour (had acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…A reliable molecular strategy was used that has been validated in recent studies, and our findings were confirmed by positive and negative controls and by amplification of several target genes as previously described. 12 The overall frequency of C. burnetii (6.4%; 54/842) in our study is lower than the overall prevalence of 10.8% (32/295) 35 in ticks along Didessa valley recently reported from Ethiopia. This difference is most probably attributed to factors like in our study a sample was considered positive when it was positive for recently developed two different types of genes (COX and IS30A spacers); however, the previous study used only one gene (IS1111 spacer).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…A reliable molecular strategy was used that has been validated in recent studies, and our findings were confirmed by positive and negative controls and by amplification of several target genes as previously described. 12 The overall frequency of C. burnetii (6.4%; 54/842) in our study is lower than the overall prevalence of 10.8% (32/295) 35 in ticks along Didessa valley recently reported from Ethiopia. This difference is most probably attributed to factors like in our study a sample was considered positive when it was positive for recently developed two different types of genes (COX and IS30A spacers); however, the previous study used only one gene (IS1111 spacer).…”
Section: Discussioncontrasting
confidence: 73%
“…The other possible factors are differences in the number of species and quantity of ticks tested, geographical locations and seasons of tick collections by the two studies might affect the prevalence. We have tested a total of 842 ticks consisting 13 different species from 9 districts in Oromia; however, the previous study 35 tested only 295 ticks comprising 7 species from one region along Didessa valley in southwest Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…and Rhipicephalus sp. collected from cattle in western Oromia and south-western Oromia, along the Didessa valley, Ethiopia (Hornok et al, 2014;Kumsa et al, 2014). However, in the Asia-Pacific region, where the clinical form of oriental theileriosis is common, Haemaphysalis spp.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 296 ticks ( Amblyomma variegatum , n = 118; A. cohaerens , n = 100; A. lepidum , n = 2; Rhipicephalus decoloratus , n = 50; R. evertsi , n = 17; R. praetextatus , n = 8 and Hyalomma rufipes , n = 1) were collected from 109 cattle belonging to 18 different herds (zebu breed) in Didessa valley, south-western Ethiopia (09°05′N, 36°33′E - 7°40′N, 36°50E) in 2012 ( Figure 1 ) [11] . Because sampling was part of the regular veterinary care and the field studies did not involve endangered or protected species, no specific permissions were required for these activities.…”
Section: Methodsmentioning
confidence: 99%
“…determine the cycle threshold (Ct) values), all tick samples were analyzed by a TaqMan based real-time PCR assay targeting the multi-copy IS 1111 insertion element of C. burnetii genome [13] . From the 32 positive samples, 8 cases ( Amblyomma cohaerens , n = 6; A. variegatum , n = 2) which harbored sufficient amount of C. burnetii DNA (Ct<35) were selected for genotyping [11] .…”
Section: Methodsmentioning
confidence: 99%